High‐frequency repetitive transcranial magnetic stimulation ameliorates memory impairment by inhibiting neuroinflammation in the chronic cerebral hypoperfusion mice - Zou, Huihui; Bao, Shilin; Chen, Xinrun; Zhou, Xianju; Zhang, Shaotian (Brain and behavior, 2024)
Background High‐frequency repetitive transcranial magnetic stimulation (HF‐rTMS) has been found to ameliorate cognitive impairment. However, the effects of HF‐rTMS remain unknown in chronic cerebral hypoperfusion (CCH). Aim To investigate the effects of HF‐rTMS on cognitive improvement and its potential mechanisms in CCH mice. Materials and methods Daily HF‐rTMS therapy was delivered after bilateral carotid stenosis (BCAS) and continued for 14 days. The mice were randomly assigned to three groups: the sham group, the model group, and the HF‐rTMS group. The Y maze and the new object recognition test were used to assess cognitive function. The expressions of MAP‐2, synapsis, Myelin basic protein(MBP), and brain‐derived growth factors (BDNF) were analyzed by immunofluorescence staining and western blot to evaluate neuronal plasticity and white matter myelin regeneration. Nissl staining and the expression of caspase‐3, Bax, and Bcl‐2 were used to observe neuronal apoptosis. In addition, the activation of microglia and astrocytes were evaluated by fluorescence staining. The inflammation levels of IL‐1β, IL‐6, and Tumor Necrosis Factor(TNF)‐α were detected by qPCR in the hippocampus of mice in each group. Results Via behavioral tests, the BCAS mice showed reduced a rate of new object preference and decreased a rate of spontaneous alternations, while HF‐rTMS significantly improved hippocampal learning and memory deficits. In addition, the mice in the model group showed decreased levels of MAP‐2, synapsis, MBP, and BDNF, while HF‐rTMS treatment reversed these effects. As expected, activated microglia and astrocytes increased in the model group, but HF‐rTMS treatment suppressed these changes. HF‐rTMS decreased BCAS‐induced neuronal apoptosis and the expression of pro‐apoptotic protein (Caspase‐3 and Bax) and increased the expression of anti‐apoptotic protein (Bcl‐2). In addition, HF‐rTMS inhibited the expression of inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α). Conclusions HF‐rTMS alleviates cognitive impairment in CCH mice by enhancing neuronal plasticity and inhibiting inflammation, thus serving as a potential method for vascular cognitive impairment. This study highlights the role and mechanisms of high‐frequency repetitive transcranial magnetic stimulation (HF‐rTMS) in chronic cerebral hypoperfusion. HF‐rTMS stimulation has been shown to attenuate cognitive impairment in mice, which is attributed to its enhancement of behavioral functions in mice by inhibiting glial cell activation, alleviating neuronal, damage, regulating synaptic proteins, and alleviating white matter damage.